Orthopaedic knowledge update. - Mont, Michael A.; Tanzer, Michael (Orthopedist) (Wolters Kluwer ; American Academy of Orthopaedic Surgeons, 2022)
"Orthopaedic Knowledge Update®: Hip and Knee Reconstruction 6 allows you to advance patient care with the best practices available. Explore the many changes in hip and knee arthroplasty in the past 5 years with updated material related to controversial topics, state-of-the-art technologies, and recent advances. The book is organized into three sections: basic and applied science relevant to both knee and hip arthroplasty; specific total knee arthroplasty topics; and specific total hip arthroplasty topics. Written by world-renowned experts in each subject, this edition features cutting-edge developments, as well as completely new chapters on thromboprophylaxis, outpatient surgery, pain management, retrieval-hip and knee, medical and biologic treatment of arthritis, nonarthroplasty management, infection, periprosthetic fracture, anatomy and surgical approaches, and dual-mobility cups and large-diameter heads for primary and revision total hip arthroplasty. Key study points are presented at the end of each chapter so you can quickly review important content. Orthopaedic surgeons with a specialty interest in hip and knee reconstruction, and physicians and allied health professionals interested in staying up to date will benefit from this edition. Residents in training can review key topics paired with helpful guidelines and images"--